Synthesis, Spectral Characterization, DNA Cleavage, and Antioxidant Properties of Metal Complexes with a Novel Schiff Base Ligand Derived from 4-Chlorobenzoic Acid - Waheed, Enass J. (Iraqi Journal of Science, 2025)
A novel Schiff base ligand (DBC) synthesized from 4-chlorobenzoic acid, along with its Cu (II) and Co (II) complexes, was prepared and characterized using FT-IR, 1H and 13C-NMR, UV-Vis spectroscopy, as well as magnetic and conductivity measurements. Based on this, a tetrahedral structure of [M(DBC)Cl2] was proposed for the complexes. Antioxidant activity of the compounds was assessed and compared to ascorbic acid, revealing that the copper complex exhibited superior antioxidant properties compared to the cobalt complex and the ligand. Furthermore, the antibiofilm potential of the copper and cobalt complexes was assessed against five clinically relevant bacterial species (P.aeruginosa, E.coli, K.pneumoniae, S.aureus and S.typhi) using various concentrations. Biofilm inhibition was quantified through optical density measurements, revealing that the copper complex had a higher mean biofilm inhibition compared to the cobalt complex at the maximum concentration of 1000 mg/ml. Optical density measurements also indicated reduced biofilm formation with increasing metal concentrations, particularly for the copper complex. Additionally, agarose gel electrophoresis showed significant alterations in plasmid DNA profiles of bacterial isolates upon exposure to the complexes, indicating potential genetic changes and implications for bacterial adaptation.